EFFECT OF MANGANESE AND ENZYMATIC DEOXYRIBONUCLEIC ACID DIGESTS ON POPULATION CHANGES AND RESPIRATION OF PNEUMOCOCCI - Firshein, William (1962)
Firshein, William (Wesleyan University, Middletown, Conn.). Effect of manganese and enzymatic deoxyribonucleic acid digests on population changes and respiration of pneumococci. J. Bacteriol. 84:478–484. 1962.—Deoxyribonucleic acid (DNA; Na salt) treated with deoxyribonuclease and Mn(++) (as MnSO(4)) stimulated R (avirulent) to S (virulent) population changes in vitro. Under certain environmental conditions and with certain strains, Mn(++) alone elicited these changes, but, in most cases, both digested DNA and Mn(++) were necessary for maximal effect. These population changes were due to a selective stimulation of the multiplication of S cells and a delay in S-cell lysis, with either a slight inhibitory effect or no effect against the multiplication of R cells. The magnitude of the population change depended upon the presence of digested DNA, the level of Mn(++), the strain, and the concentration of basal medium. Mn(++) enhanced respiration of S cells while inhibiting that of R cells.